A Randomized Prospective Comparison of Patient‐Assessed Satisfaction and Clinical Outcomes with Radioactive Seed Localization versus Wire Localization. Issue 2 (23rd December 2015) - Bloomquist, Erica V.; Ajkay, Nicolas; Patil, Sujata; Collett, Abigail E.; Frazier, Thomas G.; Barrio, Andrea V.
Abstract: Radioactive seed localization (RSL) has emerged as an alternative to wire localization (WL) in patients with nonpalpable breast cancer. Few studies have prospectively evaluated patient satisfaction and outcomes with RSL. We report the results of a randomized trial comparing RSL to WL in our community hospital. We prospectively enrolled 135 patients with nonpalpable breast cancer between 2011 and 2014. Patients were randomized to RSL or WL. Patients rated the pain and the convenience of the localization on a 5‐point Likert scale. Characteristics and outcomes were compared between groups. Of 135 patients enrolled, 10 were excluded (benign pathology, palpable cancer, mastectomy, and previous ipsilateral cancer) resulting in 125 patients. Seventy patients (56%) were randomized to RSL and 55 (44%) to WL. Fewer patients in the RSL group reported moderate to severe pain during the localization procedure compared to the WL group (12% versus 26%, respectively, p = 0.058). The overall convenience of the procedure was rated as very good to excellent in 85% of RSL patients compared to 44% of WL patients (p < 0.0001). There was no difference between the volume of the main specimen (p = 0.67), volume of the first surgery (p = 0.67), or rate of positive margins (p = 0.53) between groups. RSL resulted in less severe pain and higher convenience compared to WL, with comparable excision volume and positive margin rates. High patient satisfaction with RSL provides another incentive for surgeons to strongly consider RSL as an alternative to WL.